LEARNING RESULTS OF FRACTION MATERIAL USING A REALISTIC MATHEMATICS EDUCATION (RME) APPROACH IN PRIMARY SCHOOL STUDENTS - Ami, Rahmi Hayati; Eva Faridah; Edy Surya; Nurdin Bukit (Euclid, 2023)
This research aims to evaluate and improve student learning outcomes in fraction material by applying the Realistic Mathematics Education (RME) approach in the context of action in an elementary school. The research method used is Classroom Action Research with a research cycle consisting of planning, implementation, observation and reflection. The research location is UPTD SD Negeri 4 Bireuen. The data source in this research was class III UPTD students at SD Negeri 4 Bireuen, totaling 17 students with various levels of ability. Based on the research results, it was found that the RME approach was used for class III students at UPTD SD Negeri 4 Bireuen on simple fraction material. This is proven by the increasing number of students who complete their studies.